2022
DOI: 10.3390/ijerph19063592
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Proprioception Training on Pain Intensity in Thumb Basal Joint Osteoarthritis: A Randomized Controlled Trial

Abstract: A randomized controlled trial of forty-five females over 18 years of age with diagnosis of thumb basal osteoarthritis in their dominant hand and with a minimum pain rating of 4/10 on the Visual Analogue Scale (VAS) during activities of daily living (ADLs) were recruited from March to June 2021. The group receiving proprioception training was compared to routine conservative physiotherapy treatment. The main purpose of this clinical trial is to test the effect of proprioception training on pain intensity in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Subsequent screening of titles and abstracts resulted in 29 eligible publications for full-text assessment. Fifteen studies did not satisfy the inclusion criteria and fourteen RCTs were finally included [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The flow chart of the study selection is presented in Figure 1.…”
Section: Studies Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent screening of titles and abstracts resulted in 29 eligible publications for full-text assessment. Fifteen studies did not satisfy the inclusion criteria and fourteen RCTs were finally included [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The flow chart of the study selection is presented in Figure 1.…”
Section: Studies Selectionmentioning
confidence: 99%
“…The diagnosis of thumb CMCJ OA was confirmed using the radiographic Eaton-Littler Classification or the Modified Kellgren-Lawrence grade scale (grades 0-4, 0 = no OA) [33,34]. Three studies included patients with CMCJ OA grade 1 to 4 [26,29,32], four studies with grade 1 to 3 [20,22,23,27], three studies with grade 3 or 4 [23,27,28], two studies with grade 2 to 4 [30,31], two studies with grade 1 or 2 [21,28] and one study with grade 3 [24]. A detailed description of the study characteristics and main results are shown in Table 1.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations